An Investigation of the Relationship Between Grades and Learning Mode in an English Composition Course - Bourdeau, Debra; Griffith, Kelly; Griffith, John; Griffith, John (Journal of University Teaching and Learning Practice, 2018)
The education community has conducted studies on failure rates and withdrawal rates between learning modalities in the past, but few studies have evaluated grade distribution between learning modes or focused specifically on English Composition. Using 2,919 student grades from the 2015 – 2016 academic year for an English Composition course, researchers examined failure rates, grade distribution, and withdrawal rates between In-Person learning, Online learning, and Synchronous video learning modes. In this study, learning modes and failure rates were related. Synchronous video modes of instruction had higher failure rates than traditional In-Person classes. Synchronous video classroom students failed at a higher rate than online students. Grade distributions showed significant differences based on learning mode. In-Person students earned more Bs and fewer Cs, Ds, and Fs than Online and synchronous video classroom students. In-Person students also withdrew at a significantly lower rate than online students. With these findings, we suggest that finding the root cause and alleviating the differences in student performance across learning modes should be a high priority for the educational community.